Adjuvant (post-surgery) chemotherapy for early stage epithelial ovarian cancer - Lawrie, Theresa A; Winter-Roach, Brett A; Heus, Pauline; Kitchener, Henry C (Cochrane database of systematic reviews, 2015)
This is the second update of the review first published in the Cochrane Database of Systematic Reviews in 2009, Issue 1. Epithelial ovarian cancer is diagnosed in over 200,000 women worldwide each year. Ten to 20% of women are diagnosed early, when there is still a good possibility of cure. The treatment of early-stage (stage I and IIa) disease involves surgery to remove the disease, often followed by chemotherapy (adjuvant chemotherapy). The largest clinical trials of adjuvant chemotherapy show an overall survival (OS) advantage with platinum-based chemotherapy; however the precise role and type of this treatment in subgroups of women with differing prognoses needs to be defined. To undertake a systematic review of the evidence for adjuvant chemotherapy in early-stage epithelial ovarian cancer to determine whether chemotherapy following surgery offers a survival advantage over the policy of observation following surgery (with chemotherapy reserved for treatment of disease recurrence); and to determine if clinical subgroups of women with differing prognoses, based on histological subtype or completeness of surgical staging, have more or less to gain from adjuvant chemotherapy. We performed an electronic search using the Cochrane Gynaecological Cancer Specialized Register, Cochrane Central Register of Controlled Trials (CENTRAL 2015, Issue 3), MEDLINE (1948 to March week 5, 2015), and EMBASE (1980 to week 14, 2015). We developed the search strategy using free-text and medical subject headings (MeSH). We also searched registers of clinical trials and citation lists of included studies for potentially relevant studies. We included randomised clinical trials (RCTs) of women with early stage (I/IIa) epithelial ovarian cancer staged at laparotomy. Two review authors independently extracted data and assessed study quality of included RCTs. We resolved any disagreements by discussion with a third review author. We used random-effects methods for all meta-analyses, including subgroup analyses. The original version of this Cochrane review included five RCTs involving 1277 women. In this 2015 update, no new studies met the inclusion criteria but we included an additional paper with mature data (10-year follow-up) relating to a previously included study (ICON1).We included four studies in the meta-analyses and considered them to be at a low risk of bias. Most study participants (> 95%) had stage I ovarian cancer. Meta-analysis of five-year data from three studies indicated that women who received adjuvant platinum-based chemotherapy had better overall survival (OS) than those who did not (Hazard ratio (HR) 0.71, 95% confidence interval (CI) 0.53 to 0.93; 1008 women; 3 studies; I² statistic = 0%; high quality evidence). Likewise, meta-analysis of five-year data from four studies indicated that women who received adjuvant chemotherapy had better progression-free survival (PFS) than those who did not (HR 0.67, 95% CI 0.53 to 0.84; 1170 women, 4 studies; I² statistic = 0%; high quality evidence). These findings were robust over time, with 10-year HR estimates of 0.72 (95% CI 0.57 to 0.92; 925 women, 2 studies) and 0.67 (95% CI 0.53 to 0.83; 925 women, 2 studies) for OS and PFS, respectively (high quality evidence). The risk of death at 10 years follow-up favoured the adjuvant chemotherapy arm (0.76, 95% CI 0.62 to 0.94; 923 women, 2 studies; I² statistic = 0%), as did the findings for risk of progression at 10 years (RR 0.72, 95% CI 0.60 to 0.87; 925 women, 2 studies; I² statistic = 0%). Low quality evidence suggested that women with high-risk disease may have the most to gain from adjuvant chemotherapy. However, subgroup analyses could neither confirm nor exclude survival benefits in lower risk disease or in optimally staged disease. We found insufficient data to compare adverse events and long term risks between chemotherapy and observation groups. High-quality evidence indicates that adjuvant platinum-based chemotherapy is effective in prolonging survival in women with early stage (FIGO stage I/IIa) epithelial ovarian cancer. It remains uncertain whether women with low- and intermediate-risk early stage disease will benefit as much from adjuvant chemotherapy as women with high-risk disease. Decisions to use adjuvant chemotherapy (AC) in these women should be mindful of this uncertainty, and the uncertainty regarding adverse events. Treatment of women with lower risk disease should be individualised to take into account individual factors.